SURVIVAL DIFFERENCES OF LOW BIRTH WEIGHT BASED ON SOCIO-ECONOMIC FACTORS - Ruliyani, Hanin; Lestari, Novi; Indriani, Diah (Universitas Airlangga, 2024)
IDHS 2017 showed the prevalence of low birth weight (LBW) infants in Indonesia is 7%. LBW can increase the risk of mortality, morbidity, and growth disorders. The survival of LBW infants can be influenced by socioeconomic factors. The purpose of this study is to analyze survival time differences of LBW infants based on socioeconomic factors. This research is a non-reactive study using secondary data from the IDHS 2017. Survival analysis using the Kaplan-Meier method and analysis of differences in survival curves using the Log Rank method. The independent variables in the study include parents' occupation, household wealth index, mother's education, and father's education. The measured event is infant mortality within one year. Mother's education (p value=0.069) has no difference in the survival time of LBW. The parent's occupation (p value=0.013) has a difference in the survival time of LBW. The probability of survival is 99% in LBW with non-working mothers. There is a difference in the survival time of LBW based on the household wealth index factor (p value=0.000) with the probability of survival for LBW born in the lowest wealth index family is 90%. Differences in the survival time of LBW have been found in the parents' occupation and household wealth index variables.